Medical research by the British Antarctic Survey - Edholm, O. G. (Polar Record, 1965)
There is a long record of medical research and observation in the Antarctic, almost as long as the record of exploration. The early expeditions usually had a medical officer who described the medical hazards of the Antarctic. In this article, an account will be given of the research undertaken by medical officers of the Falkland Islands Dependencies Survey (FIDS) and, subsequently, of the British Antarctic Survey (BAS). A more detailed report will be found in the chapter entitled “Man and the environment” in Antarctic research (Priestley et al. eds, 1964).